Precipitating convective cloud downdraft structure: a synthesis of observations and modeling - Knupp, Kevin Robert, author; Cotton, William R., advisor; Brown, John M., committee member; Stevens, Duane E., committee member; Sinclair, Peter C., committee member; Bienkiewicz, Bogusz, committee member (Colorado State University. Libraries, 1985)
This study represents a comprehensive investigation in which observations are integrated with three-dimensional cloud model results to examine the kinematic, dynamic and thermodynamic structure of downdrafts associated with precipitating convection. One particular downdraft type, the low-level precipitation-associated downdraft, is investigated in considerable detail. It is shown that this downdraft exhibits significant structural, dynamic and thermodynamic properties which differ appreciably from other independent downdrafts within precipitating convective clouds. General airflow and trajectory patterns within low-level downdrafts are typically convergent from ~0.8 km upwards to downdraft top, typically less than 5 km AGL. Observed mass flux profiles often increase rapidly with decreasing height as a result of strong buoyancy forcing below the melting level. Such patterns indicate that strong cooling by melting and evaporation within statically unstable low levels generates low perturbation pressure by virtue of buoyantly-induced pressure perturbations. Cloud model results verify this process and indicate that pressure perturbations are strongest during downdraft developing stages. Maximum modeled pressure reductions up to 2 mb are located within downdrafts and precipitation about 0.6 km below the 273 K level approximately 10 min after heavy precipitation (˃ 2 g kg¯¹) enters low levels. The magnitude of this buoyantly-produced pressure reduction is influenced by temperature, static stability, relative humidity and precipitation characteristics. Model results and related calculations indicate that cooling provides the impetus for downdraft formation. Melting, in particular is generally found to make significant contribution to total cooling in cases having relatively shallow (˂ 2 km) PBL. Cooling by evaporation becomes increasingly important as PBL depth increases. Inflow to the low-level downdraft, although vertically continuous, can be separated into two branches. The up-down branch originating within the PBL initially rises up to 4 km and then descends within the main precipitation downdraft. The midlevel branch, most pronounced during early downdraft stages, originates from above the PBL and transports low-valued ϴₑ to low levels. Pressure forces important along both branches act to lift stable air along the up-down branch, and provide downward forcing of positively-buoyant air in the upper regions of both branches. Two primary conclusions are drawn from the results of this study: (1) Downdrafts are driven at low levels within regions of strong static instability by strong cooling provided by melting and evaporation. Cloud level entrainment effects make secondary contributions. (2) Precipitation size and phase (e.g. melting) are probably the most important controlling parameters for downdraft strength.
Original is missing pages 241, 261, and 277.
Keywords: Convective clouds